The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages A National Health Service The proposals set out below for a National Health Service were endorsed unanimously by the Conference :— The present "hotch-potch" of health services — National Health Insurance with dozens of Approved Societies, with restricted and varying range of benefits, confined to only wage earners ; separate School Medical Service ; Voluntary and Municipal Hospitals ; Nursing Homes dependent for their maintenance on charity ; private practitioners working for profit alongside of public Medical Officers — must as early as possible be replaced by a comprehensive National health Service. Such a Health Service must be: (a) Free of charge to all people in its entirety. (b) Inclusive of all forms of medical, surgical and specialist service and treatment without exception. (c) Staffed by full-time salaried doctors, nurses and other health workers — all entitled to superannuation. The existing voluntary and municipal hospitals would all pass into a unified and democratically controlled hospital system. Local practitioners' services would be based upon the local Health Centre, and would afford to the patient at least as wide a freedom of choice of doctors as at present free of charge, and under vastly superior conditions. At all levels the Service would be controlled democratically by elected representatives of the people, but managed in the main by the Health workers themselves. The conditions of service of all health workers would be raised to a uniform level commensurate with the skill and arduous nature of the profession. The Beveridge Plan must be implemented in full to provide minimum living standards as a necessary and the best safeguard against ill-health. The Communist Party support the general lines of the Labour Party's proposals for a National Health Service, and believes that all working class and progressive forces must now organise a big campaign to defeat the reactionary forces which are opposing or attempting to whittle down the Beveridge Plan and the National Health Service. 32 15X/2/103/295